2005
DOI: 10.1105/tpc.105.031856
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Peroxisomal Citrate Synthase Is Required for Fatty Acid Respiration and Seed Germination

Abstract: We tested the hypothesis that peroxisomal citrate synthase (CSY) is required for carbon transfer from peroxisomes to mitochondria during respiration of triacylglycerol in Arabidopsis thaliana seedlings. Two genes encoding peroxisomal CSY are expressed in Arabidopsis seedlings, and seeds from plants with both CSY genes disrupted were dormant and did not metabolize triacylglycerol. Germination was achieved by removing the seed coat and supplying sucrose, but the seedlings still did not use triacylglycerol. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
173
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 52 publications
8
173
0
4
Order By: Relevance
“…Pracharoenwattana et al (2005) suggested an essential role for lipid respiration in seed germination, since a double mutant in two of the peroxisomal citrate synthase isoenzymes led to a dormant seed phenotype. An additional energy resource is necessary in dark-treated plants for maintenance of metabolism, since at the end of the regular night period transitory starch is basically exhausted (Smith and Stitt, 2007).…”
Section: Fatty Acid Degradation In the Dark Is Essential For Providinmentioning
confidence: 99%
See 1 more Smart Citation
“…Pracharoenwattana et al (2005) suggested an essential role for lipid respiration in seed germination, since a double mutant in two of the peroxisomal citrate synthase isoenzymes led to a dormant seed phenotype. An additional energy resource is necessary in dark-treated plants for maintenance of metabolism, since at the end of the regular night period transitory starch is basically exhausted (Smith and Stitt, 2007).…”
Section: Fatty Acid Degradation In the Dark Is Essential For Providinmentioning
confidence: 99%
“…Moreover, analyses of mutants deficient in two of the peroxisomal citrate synthases (csy2 csy3) suggested an important function for b-oxidation in fatty acid respiration in addition to gluconeogenesis via the glyoxylate cycle (Pracharoenwattana et al, 2005). Expression of both citrate synthases was strongly increased in leaves of plants exposed to extended darkness (van der Graaff et al, 2006), whereas the glyoxylate cycle key enzymes isocitrate lyase and malate synthase remained at a low level of expression.…”
Section: Introductionmentioning
confidence: 99%
“…From the onset of germination (radicle emergence from the seed coat), this reserve is mobilized in order to support growth during early seedling development [11][12][13][14]. The presence of glyoxylate cycle and -oxidation enzymes, especially abundant during post-germination growth, leads to the breakdown of storage lipids to be used directly in respiration and in the synthesis of carbohydrates [11,15]. The incorporation of these soluble molecules at the level of citrate in the tricarboxylic acid cycle allows the growing of seedlings until photoautotrophic growth occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The Brassicaceae Arabidopsis thaliana, frequently used as a model system in genetics and plant development works, has been studied for regulation of flavonoid gene expression [22,23] and lipid breakdown [15,24] in seeds and germinating seedlings. Previous work with B. oleracea sprouts concerned the genetic characterization of seed germination [25,26], monitorization of cell cycle modifications during the first divisions of the seeds [6], sensitivity to hypoxia [18], and the ability of seeds produced under a drought to germinate normally [27].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, peroxisomal citrate synthase (CSY2 and CSY3) transcripts are expressed throughout the flower (Zimmermann et al, 2004), suggesting that lipids can be used as a source of carbon for respiration, as has been proposed for germinating sunflower (Helianthus annuus) seeds (Reymond et al, 1992). In this scenario, acetyl-CoA produced by b-oxidation is converted to citrate, which is exported from the peroxisome and participates in the citric acid cycle (Pracharoenwattana et al, 2005). Thus, products of fatty acid catabolism can pass from the peroxisome to the mitochondrion independently of the glyoxylate cycle, as is the case in Arabidopsis mutants, which lack isocitrate lyase (Eastmond et al, 2000).…”
Section: Pollen Tube Germination and Growth Are Impaired In Cts Mutantsmentioning
confidence: 99%